Post occupancy evaluation of private schools in Shah Alam / Suhaila Hanapiah - Hanapiah, Suhaila (2013)
Post Occupancy Evaluation (POE) has used to evaluate building performance criteria by auditing user feedbacks. A POE was conducted to measure the performance of two numbers of selected private schools in Shah Alam in the line of the aims that is to determine user's satisfaction on the building performance. Empirical Review of Past POE Studies shows that there have differences building performance criteria for different type of building. In evaluating building performance criteria, there has fifteenth criteria were identified from literature that needed in a building for better performance. The building owner and users were interview to obtain their feedbacks on five building elements namely cleanliness, visual comfort, thermal comfort, security service and noise comfort. The outcome indicates that natural lighting at Sekolah Integrasi Al-Fikr Bistari is poor with the numbers of 45% respondents at this school were dissatisfied. Natural lighting is one of the parameters of visual comfort aside from artificial lighting. The others elements namely cleanliness, thermal comfort, security and noise comfort at Sekolah Integrasi Al-Fikr Bistari are in good condition because these elements were satisfied the respondents. Meanwhile, the Integrated Islamic School Shah Alam indicates that noise comfort around the school dissatisfied the 27% of respondents. There has the good performance on the building elements of visual comfort and thermal comfort with higher rating percentage of respondents towards these two elements. From the result, it is shows that both schools has good performance but somehow there need in improving their facilities to give better performance to the building in order to improve the user's performance in future.